2013
DOI: 10.4103/2249-4863.123777
|View full text |Cite
|
Sign up to set email alerts
|

Referral letter with an attached structured reply form: Is it a solution for not getting replies

Abstract: Background:Communication between primary care doctors and specialists/hospital doctors is vital for smooth functioning of a health care system. In many instances referral and reply letters are the sole means of communication between general practitioners and hospital doctors/specialists. Despite the obvious benefits to patient care, answers to referral letters are the exception worldwide. In Sri Lanka hand written conventional letters are used to refer patients and replies are scarce.Materials and Methods:This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…PH2 scored 0% and Referral / Counter referral form 3.9%. Similar results were obtained in the study that was conducted in Sri Lanka showing that only 7.5% of the referral feedback was received [ 37 ]. Contrary, an improvement was observed regarding referral feedback in the updated formats with 53.9% for ANC, delivery and PNC external transfer letter, and 42.6% for the external transfer form.…”
Section: Discussionsupporting
confidence: 86%
“…PH2 scored 0% and Referral / Counter referral form 3.9%. Similar results were obtained in the study that was conducted in Sri Lanka showing that only 7.5% of the referral feedback was received [ 37 ]. Contrary, an improvement was observed regarding referral feedback in the updated formats with 53.9% for ANC, delivery and PNC external transfer letter, and 42.6% for the external transfer form.…”
Section: Discussionsupporting
confidence: 86%
“…Although 70% of the specialists admitted that they reply to referral letters always or most of the time, this is contrary to the views of general practitioners. (12,13,14) This interactive process should be balanced and mutual and this will result only if both primary care doctors and specialists respect each other. (6) Several studies have revealed lack of respect for GPs by specialists (8,15,16) and the Canadian RESPECT study (15) suggested that this could be improved by creating better relationships between GPs and specialists, enhancing profile of family medicine in Universities and teaching hospitals and by changing negative attitudes by promoting the expertise and role of family medicine.…”
Section: Discussionmentioning
confidence: 99%
“…A referral process that is practiced efficiently, can contribute to high standards of care, improving patient's outcomes and assists in making cost-effective use of hospitals and primary health care services through optimal use of medical services. (5)(6)(7). It can also support health centers and outreach services by experienced staff from the hospital and helps build capacity and enhance access to better quality care (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%